PRO-INFLAMMATORY BIOMARKERS AND CYTOKINES IN THE VARIOUS STAGES OF OSTEOARTHRITIS (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Studies have shown, the burden and impact of OA in India are substantial and it is increasing. The current pilot study compared the levels of biomarkers in cases to those in healthy controls and within grades.Materials and method: 95 subjects between the ages of 40 and 75 were a part of the study. Out of 95, knee OA cases were 63, and normal healthy subjects were 32. It also assessed the relationship between proinflammatory cytokines and biomarkers (IL-6, TNF-a, CTX-I, and CTX-II) from patients with Kellegren-Lawrence grades 1-4. Chi-square, Mann-Whitney U test, correlation, and ROC were used for comparison, and association, to find sensitivity, specificity, and predictive values.Result: 20% of the participants were in stage 3 and 4 categories of K-L grade. Cases showed significantly higher levels of IL-6, TNF-α and CTX-I compared to controls. A consecutive significant (p = .04) increase was observed with mean IL-6 within 4 grades of OA while mean TNF-α showed an increase in 3rd and 4th grade as compared to 1st and 2nd grade (P = .01). Conclusion: From the ROC curve, the biomarkers (IL-6, TNF-α, CTX-I and TNF-α, and IL-6 together) are good predictors of Severe OA. The highest predictive value was observed with IL-6 and TNF-α a together. There is a need for research, development, Quantification, and application of biomarkers with large sample sizes. A tool is required for the validation of biomarkers in OA.